From Where the Foot Steps: Choral Autoethnography and Rhizomatics of Disability (Andamios, Revista de Investigación Social, 2025)
The article presents the autoethnography co-produced by two researchers narrating their experiences of disability. The objective of this research is to focus on analyzing and interpreting our history with disability through the axes of positioning, emotions, reflexivity and subjectivation. The state of the matter reflects the scarce academic production around the axes, its distribution in geocultural spaces, as well as representation by gender and authorship. During a year of work, events, memories and categories were identified in joint writing. The results and conclusions show similarity and differences, not only in our stories but in their meaning in our family and cultural contexts.
Keywords: Autoethnography; disability; positioning; reflexivity; subjectivity